2012
DOI: 10.1007/978-3-642-30726-3_19
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Drug Therapy for Oncologic Diseases

Abstract: There are clear gender-dependent differences in response rates and the probability of side effects in patients treated with chemotherapy. Sex-biased expression levels of metabolic enzymes and transporters in liver and kidney leading to different pharmacokinetics have been described for most common anti-cancer drugs. In women, half-life is often longer, which is associated with improved survival, but also increased toxicity.Some chemotherapy protocols lead to a better response rate in women without increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 140 publications
2
72
0
Order By: Relevance
“…This is the first demonstration of a gender difference in CDA-expression and its impact on 5-azacytidine or decitabine treatment outcomes, however, greater efficacy, but also greater toxicity in females for a number of other cancer drugs has been documented, associated with lower expression in females of liver or kidney metabolic enzymes and transporters relevant to metabolism of these drugs (reviewed in(46)). The specific mechanisms or reasons underlying this broad gender-bias in expression of metabolic enzymes have not been characterized.…”
Section: Discussionmentioning
confidence: 91%
“…This is the first demonstration of a gender difference in CDA-expression and its impact on 5-azacytidine or decitabine treatment outcomes, however, greater efficacy, but also greater toxicity in females for a number of other cancer drugs has been documented, associated with lower expression in females of liver or kidney metabolic enzymes and transporters relevant to metabolism of these drugs (reviewed in(46)). The specific mechanisms or reasons underlying this broad gender-bias in expression of metabolic enzymes have not been characterized.…”
Section: Discussionmentioning
confidence: 91%
“…All of the above findings suggest that oestrogen has a prominent role in preventing the development of colorectal cancer. Moreover, antibodies have a longer half-life in women, resulting in an improved response to treatment with monoclonal antibody (22). Wakelee and associates examined the effects of age and gender on the survival of patients with NSCLC with and without bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies of sunitinib and sorafenib found no clinically relevant differences in sex to warrant dose adjustments, and sorafenib phase 3 trials found no differences in toxicity. 24,25 However, bevacizumab was found to have pharmacokinetic variability based on sex. 26 Although sex has not appeared to affect the efficacy of VEGF-targeted therapies, 25 further research should be performed to determine the true impact of sex on toxicity.…”
Section: -419-21mentioning
confidence: 99%